Regulation of inflammatory pathways by cannabigerol in the collagen induced arthritis model in rats - Šteigerová, Monika; Sklenárová, Michaela; Bazyuk, Mykhaylo; Záveský, Luděk; Jelínek, Petr; Arora, Mahak; Stránský, Daniel; Kučera, Tomáš; Sepodes, Bruno; Šoóš, Miroslav; Šíma, Martin; Slanař, Ondřej (Frontiers in Pharmacology, 2025)
ObjectivesThis study aims to assess the anti-inflammatory properties of cannabigerol (CBG) in collagen-induced arthritis (CIA) model in rats, and to determine which inflammatory signaling pathways it affects.Study designRats were randomized into four groups: placebo (PCB)–p.o. Treated with 1 mL of 0.9% saline once daily, CBG–p.o. Treated with 30 mg of CBG/day, glucocorticoids (GC)–p.o. Treated with methylprednisolone 0.5 mg/kg/day, and negative control (CO)–p.o. Treated with 1 mL of 0.9% saline once daily. CIA was induced in the PCB, GC, and CBG groups. The effect of CBG was assessed by clinical scoring, paw width measurements, ELISA, and analysis of gene (qPCR) and protein (Western blot) expression of selected inflammatory markers in blood and synovial membrane.ResultsClinical scores showed significant improvement in the CBG vs. PCB on day 29 and in the GC vs. PCB on days 24, 27, and 29. MMP-3 levels in serum were significantly reduced in the GC vs. PCB. CBG demonstrated a selective anti-inflammatory and immunomodulatory profile, notably through the downregulation of key signaling molecules such as TLRs, systemic NF-κB p65, STAT-3, and inflammasome-related components including NLRP1A, NLRP3, AIM2, gasdermin D, and caspase-1. It also reduced IL-1β and TNF expression during the early phase of disease and increased expression of the anti-apoptotic gene BCL-2.ConclusionOur findings indicate that CBG modulates distinct components of the inflammatory signaling pathways, and its effects translated into significant improvement in clinical scoring based on swelling, erythema, stiffness in rat CIA model.